THE EFFECT OF Bacillus sp. ADDITION ON THE VIRULENCE OF Vibrio parahemolyticus TOWARD AXENIC CULTURE OF Artemia franciscana - Ni Luh Komang Ayu Maitri Jayanthi; Pande Gde Sasmita Julyantoro; Dewa Ayu Angga Pebriani (Journal of Fish Health, 2022)
Research on the benefits of Bacillus sp. in aquaculture has been done a lot. Currently, the aquaculture industry, especially shrimp farming, is facing AHPND disease, which is known to be caused by Vibrio parahaemolyticus. This study aims to see the effect of Bacillus sp. against virulence of V. parahaemolyticus in vitro using caseinase production as an indicator and survival of Artemia franciscana cultured axenically when challenged with V. parahaemolyticus. In in vitro tests, cultures of V. parahaemolyticus were grown with and without the addition of Bacillus sp. on Luria Bertani (LB) liquid media, and then the caseinase test was carried out using skim milk (SM) agar as a growth medium. In the challenge test, 10 axenic cultured Artemia sp. were distributed in falcon tubes containing 10 ml of sterile seawater. Challenge test treatments consisted of treatment A as control of Artemia culture without the addition of bacteria, treatment B Artemia culture adding by 106 CFU/ml V. parahaemolyticus, treatment C Artemia culture with the addition of 106 CFU/ml Bacillus sp., and treatment D Artemia culture with the addition of 106 CFU/ml V. parahaemolyticus and 106 CFU/ml Bacillus sp. All treatments were done in triplicates. The results showed that the addition of Bacillus sp. was able to reduce the caseinase production of V. parahemolyticus up to 29% indicated by the decrease of the clearing zone diameter formed on SM agar. Furthermore, the addition of Bacillus sp. in treatment D was able to significantly increasing (P<0.05) of Artemia's survival when challenged with V. parahamolyticus. This indicates that Bacillus sp. has a potential as a probiotic candidate to prevent disease caused by V. parahaemolyticus.